Should the Federal Reserve Issue a Digital Currency as Virtual Legal Tender? An Econo-legal Analysis Based on China’s Master Plan for De-dollarization - Hung, Alvin Hoi-Chun (American Journal of Trade and Policy, 2023)
Mainstream discussion on whether the Federal Reserve should issue a central bank digital currency (CBDC) as virtual legal tender focuses on five aspects related to the American domestic environment -- efficiency, privacy, safety and security, financial inclusion and exclusion, and impact on the current economic systems and monetary policies. This article takes a new and broader perspective on this critical issue by investigating how China, being the arch-international competitor of the US, has formulated a well-designed and structured master plan supported by various econo-legal strategies to pursue the objective of de-dollarization through the utilization of a China-currency-based CBDC with “controllable anonymity” and different multicurrency exchange and settlement platforms. Given the reality that de-dollarization will inevitably weaken the ubiquitous platform of international trade and payment of the US dollar (USD), can the Federal Reserve use the same tool, a USD-based CBDC, to counteract or even reverse the declining trend of the American currency’s versatility and far-reaching capability? This article recommends that the Federal Reserve can slow down the de-dollarization movement by issuing a CBDC at both the wholesale and retail levels, emphasizing the control of the former while having more cooperation with private banks for the latter.
Keywords: Central Bank Digital Currency; Legal Tender; Federal Reserve; Dollarization; De-Dollarization